Pembuatan Pupuk Organik Cair Guna Mengurangi Penggunaan Pupuk Anorganik Oleh Masyarakat Di Lembang Turunan - Andri Yanto Saul; Leony Bara’ Tau Pasang; Agustinus Mantong (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2021)
The problems that arise due to the use of inorganic fertilizers are quite complex. Soil pollution, economic problems for the community around Lembang Derunan, as well as a decrease in agricultural yields due to the long-term impact of the use of inorganic fertilizers. This occurs due to a lack of public awareness and ignorance regarding the use of organic fertilizer. The aim of making liquid organic fertilizer is to increase public awareness in Lembang Derivatives and overcome problems that arise due to the use of organic fertilizer. Based on the results of this research, it was found that liquid organic fertilizer materials are easy to find and can overcome people's problems in providing fertilizer for plants, especially rice. Rice with liquid organic fertilizer has been proven to be more fertile and able to maintain soil quality compared to rice without organic fertilizer